Rituály přijetí dítěte do lokální komunity : Obec Peristerona - jihozápadní část Kypru - Jeřábková, Petra (Lidé města, 1999)
As part of a research of transition rituals in the Cypriot mountain village of Peristerona I watched the act of baptism and its formal course, content and social impact. This paper focuses on symbolical acts of acceptation of a child both into the community of the Orthodox church and the broader village community. Peristerona is an agricultural village with about 200 permanent residents. Although the village residents have a very close relationship with the nearby town, they have also very close ties with their family, insist on neighbourly relationships, and preserve a number of traditional ceremonies and rituals. Tradition supports a ritual which consists of the acceptation of a child into the closest family, the local community as well as the Orthodox church. A child is accepted into the closest family immediately after its birth and this act is an independent ritual. On the other hand, acceptation into the church and the village community is postponed to a later time, but six months after the birth of the child at the latest. Both rituals make part of a single, comprehensive ritual, which includes the selection of a godfather, a religious ritual in church with an active role played by the priest and the godfather, the ritual of acceptation by the village community connected with a feast and, last but not least, the protection and observation of a child in the transient period which lasts another three days after the baptism is made. Baptism is the most important act in the life of every individual. Without baptism one cannot undergo further vital events in life such as the church wedding or legally valid burial. Baptism is also a vital step for the inclusion of an individual into the local village community. The child is not regarded as a fully-fledged member of a village community unless it is baptised. However, baptism is not only viewed as the acceptation of a child by the Orthodox church and the village community. It also amounts to the creation of a secondary family background the child obtains in godfather's family. The whole process of the acceptation of a child into a local community is gradual and lasts several days. The child is finally included into it only after three days, after the transient period ends. After three days the child is bathed and finally included into the village community without any further acceptation rituals.